Public space, collective memory and intercultural dialogue in a (UK) city of culture. Issue 5 (2nd September 2016) - McDermott, Philip; Nic Craith, Máiréad; Strani, Katerina
Abstract : Using the case study of Derry~Londonderry and its designation as 'UK City of Culture 2013', the primary objective of this research paper is to critically analyse the challenges associated with the production of a year-long cultural programme in a culturally and politically divided place. Given that Northern Ireland's second largest city has been understood in terms of a conflict between 'two traditions', Irish/Catholic and British/Protestant, we critically assess the dialogue and policy negotiations with reference to public places as well as representations of collective memory and traditional music during the year. Fieldwork over two years has enabled us to investigate how culture and identity politics are played out in the context of a city undergoing a process of reconciliation. Placing our case study in a strongly comparative context, we argue that cultural concerns are pivotal points of (re-)negotiation in any society transitioning from conflict to 'peace' and that this issue, therefore, is of vital concern to academics and policymakers alike internationally.